Modelling Methodologies: Opportunities and Limits - Mehaffy, Michael West (A+BE | Architecture and the Built Environment, 2015)
This chapter describes in detail the methodologies of modelling and their limits, as a preparation for exploring the specific model to be proposed and evaluated.